Commercialisation and commodification of breastfeeding: video diaries by first-time mothers - Alison M. Taylor; Jo Alexander; Edwin van Teijlingen; Kath M. Ryan (BMC, 2020)
Abstracts Background Many of aspects of our lives became increasingly commercialised in post-modern society. Although breastfeeding is perhaps a late comer to this process in recent years, it too has seen significant commercialisation facilitated by social media and our obsession with celebrity culture. This paper explores how the commercialisation and commodification of breastfeeding impacts mothers' experiences of breastfeeding. Methods In a qualitative study, five mothers in the United Kingdom recorded their real-time breastfeeding experiences in video diaries. Using a multi-modal method of analysis, incorporating both visual and audio data, a thematic approach was applied. Findings Women preparing for breastfeeding are exposed to increasing commercialisation. When things do not go to plan, women are even more exposed to commercial solutions. The impact of online marketing strategies fuelled their need for paraphernalia so that their dependence on such items became important aspects of their parenting and breastfeeding experiences. Conclusions The audio-visual data demonstrated the extent to which "essential" paraphernalia was used, offering new insights into how advertising influenced mothers' need for specialist equipment and services. Observing mothers in their video diaries, provided valuable insights into their parenting styles and how this affected their breastfeeding experience.